Targeting β-glucans, vital components of the Pneumocystis cell wall - Wang, Mengyan; Zhang, Zhongdong; Dong, Xiaotian; Zhu, Biao (Frontiers in Immunology, 2023)
β-glucan is the most abundant polysaccharide in the cell wall of Pneumocystis jirovecii, which has attracted extensive attention because of its unique immunobiological characteristics. β-glucan binds to various cell surface receptors, which produces an inflammatory response and accounts for its immune effects. A deeper comprehension of the processes by Pneumocystis β-glucan recognizes its receptors, activates related signaling pathways, and regulates immunity as required. Such understanding will provide a basis for developing new therapies against Pneumocystis. Herein, we briefly review the structural composition of β-glucans as a vital component of the Pneumocystis cell wall, the host immunity mediated by β-glucans after their recognition, and discuss opportunities for the development of new strategies to combat Pneumocystis.